Proceedings of the Sixth International Workshop on Natural Language Processing for Social Media 2018
DOI: 10.18653/v1/w18-3512
|View full text |Cite
|
Sign up to set email alerts
|

Improving Classification of Twitter Behavior During Hurricane Events

Abstract: A large amount of social media data is generated during natural disasters, and identifying the relevant portions of this data is critical for researchers attempting to understand human behavior, the effects of information sources, and preparatory actions undertaken during these events. In order to classify human behavior during hazard events, we employ machine learning for two tasks: identifying hurricane related tweets and classifying user evacuation behavior during hurricanes. We show that feature-based and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Our infrastructure was recently used in one of our research studies [33] to help identify evacuation behavior to create a training set for automated detection of evacuation behavior based both on textual clues in a user's tweets as well as their physical movements. The tool is currently deployed for various research efforts associated with [1] and continues to prove itself a stable, scalable social media post collection infrastructure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our infrastructure was recently used in one of our research studies [33] to help identify evacuation behavior to create a training set for automated detection of evacuation behavior based both on textual clues in a user's tweets as well as their physical movements. The tool is currently deployed for various research efforts associated with [1] and continues to prove itself a stable, scalable social media post collection infrastructure.…”
Section: Resultsmentioning
confidence: 99%
“…In practice, we have found that these locations may not be homes but instead gyms, work, or school. We found, however, that the accuracy of a home location is not as important as the identification of a location that represents normalcy during non-storm times [33]. Figure 3 shows the user's calculated home location as a transparent blue circle.…”
Section: Clustering Home Location and Movementmentioning
confidence: 94%
“…We plan to further complement this research by analyzing tweets from Twitter communities that discuss different topics. In this regard, techniques such as domain adaptation, transfer learning, active and online learning could help models to adapt to new domains and address issues associated with the lack of training data (Johnson et al 2020 ; Kaufhold et al 2020 ; Stowe et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Outside the social media domain, Velichkov et al (2019) investigate models to predict the outcome of sports events from interviews conducted shortly before the event. Within social media, Stowe et al (2018) present models to determine whether people evacuate during a hurricane event from their tweets. Finally, Swamy et al (2017) present a framework to forecast winners of events (e.g., sports events, elections, awards) by aggregating predictions made by individual users.…”
Section: Previous Workmentioning
confidence: 99%